Evaluation of the effects and consequences of major accidents in industrial plants - Casal, Joaquim (Elsevier, 2008)
The book analyzes the different major accidents which can occur in process plants and during the transportation of hazardous materials. The main features of fires, explosions and toxic releases are discussed, and a set of mathematical models allowing the prediction of their effects and consequences are explained. With a practical approach, the models are applied to simple illustrative examples, as well as to more complex real cases. The use of these calculations in the frame of Quantitative Risk Analysis is also treated. Evaluation of the effects of major accidents in industrial installations covers the following topics: general introduction, source term, fire accidents, vapour cloud explosions, BLEVEs and vessel explosions, atmospheric dispersion of toxic or flammable clouds, vulnerability, and quantitative risk analysis. This book is a useful tool for engineering professionals, as well as an interesting reference for teaching at graduate and post-graduate levels. Both the essential aspects and the calculations related to the diverse accidents are discussed The prediction of effects and consequences is performed with a practical approach Recent contributions from literature have been included Subjects of increasing importance have been included: an extense analysis of BLEVEs, for example, or the atmospheric dispersion of pathogenic agents.
Keywords: Industrial accidents.; Industrial accidents -- Mathematical models.; elektronické knihy; electronic books